Measurements of branching fractions for B0→Ds+π- and B̄0→Ds+K- - Das, A; Aziz, T; Trabelsi, K; Mohanty, G; Adachi, I; Aihara, H; Arinstein, K; Aulchenko, V; Aushev, T; Bakich, A; Balagura, V; Barberio, E; et al. (2010)
We present improved measurements of the branching fractions for the decays B0→Ds+π- and B̄0→Ds+K- using a data sample of 657×106 BB̄ events collected at the Υ(4S) resonance with the Belle detector at the KEKB asymmetric-energy e +e- collider. The results are B(B0→Ds+π -)=(1.99±0.26±0.18)×10-5 and B(B ̄0→Ds+K-)=(1.91±0.24±0.17) ×10-5, where the uncertainties are statistical and systematic, respectively. Based on these results, we determine the ratio between amplitudes of the doubly Cabibbo suppressed decay B0→D+π- and the Cabibbo favored decay B0→D-π+, R Dπ=[1.71±0.11(stat)±0.09(syst)±0.02(theo)]%, where the last term denotes the theory error. © 2010 The American Physical Society.